Ethics Training Is Essential for Environmental Laboratories. Issue 9 (3rd November 2021) - Adams, Hunter; Wangsness, Kathryn; Johnson, Mary; Olund, Shane; Loudon, Jennifer; Hertz, Charles D.; Morin, Erin
Key Takeaways: Ethics is a guiding moral philosophy for decision‐making and is part of a sound quality assurance/quality control program; likewise, data integrity must be rooted in sound principles. Analysts at water, wastewater, and public health laboratories owe it to their profession and the public to always maintain data integrity, otherwise risking potentially serious consequences. Steps can be taken to better ensure ethical laboratory practices, such as ethics training, data review, policies, codes of ethics, and internal audits.